Ethnobotanical study of medicinal plants used to treat human diseases in Gura Damole District, Bale Zone, Southeast Ethiopia (Asian Journal of Ethnobiology, 2021)
Abstract. Assefa B, Megersa M, Jima TT. 2021. Ethnobotanical study of medicinal plants used to treat human diseases in Gura Damole District, Bale Zone, Southeast Ethiopia. Asian J Ethnobiol 4: 42-52. Many countries, including Ethiopia, use medicinal plants for their primary health care system. Plants have been used as a source of medicine to treat human diseases in Ethiopia. This study aimed to document medicinal plants to treat various human diseases in southeast Ethiopia's, the Gura Damole District of Oromia Regional State. Ethnobotanical survey of medicinal plants was carried out from August 05 to November 06, 2019. A total of 90 informants were selected to collect ethnobotanical information from 6 kebeles. Ethnobotanical data were collected using semi-structured interviews, focus group discussions with informants, and field observation. Various ethnobotanical ranking indices were used to analyze the importance of some plant species. A total of 30 medicinal plants belonging to 21 families were identified. These medicinal plants comprised shrubs (36.6%), trees (26.6%), herbs (23.3%), and lianas (13.3%). The plant families with the highest medicinal plants in the study area used for various diseases treatment were Asteraceae and Solanaceae (3 species each). Leaves (46.7%) were the dominant plant part used to prepare remedies, followed by roots (36.7%). Powdering (50%) and oral route of administration (59%) were commonly mentioned methods of preparation and administration, respectively. Carissa spinarum was the most preferred medicinal plant to treat evil eyes and is also ranked highest as the preferable medicinal plant for various purposes. Although the current study revealed the existence of indigenous knowledge of medicinal plants to treat human diseases, agricultural expansion became the primary threat to medicinal plants. Hence, different conservation methods should be applied to conserve those mostly preferred and frequently used medicinal plants for various purposes.
Keywords: Gura Damole; indigenous knowledge; medicinal plants; preparations; traditional medicine